Pivotal Cytoprotective Mediators and Promising Therapeutic Strategies for Endothelial Progenitor Cell-Based Cardiovascular Regeneration - Hyunyun Kim; Sujin Kim; Sang Hong Baek; Sang-Mo Kwon (Stem Cells International)
Cardiovascular diseases (CVDs), including atherosclerosis, stroke, and myocardial infarction, is a major cause of death worldwide. In aspects of cell therapy against CVD, it is generally accepted that endothelial progenitor cells (EPCs) are potent neovascular modulators in ischemic tissues. In response to ischemic injury signals, EPCs located in a bone marrow niche migrate to injury sites and form new vessels by secreting various vasculogenic factors including VEGF, SDF-1, and FGF, as well as by directly differentiating into endothelial cells. Nonetheless, in ischemic tissues, most of engrafted EPCs do not survive under harsh ischemic conditions and nutrient depletion. Therefore, an understanding of diverse EPC-related cytoprotective mediators underlying EPC homeostasis in ischemic tissues may help to overcome current obstacles for EPC-mediated cell therapy for CVDs. Additionally, to enhance EPC’s functional capacity at ischemic sites, multiple strategies for cell survival should be considered, that is, preconditioning of EPCs with function-targeting drugs including natural compounds and hormones, virus mediated genetic modification, combined therapy with other stem/progenitor cells, and conglomeration with biomaterials. In this review, we discuss multiple cytoprotective mediators of EPC-based cardiovascular repair and propose promising therapeutic strategies for the treatment of CVDs.